Negative electrode plate, secondary battery, battery module, battery pack, and power consumption device

The dual coating structure on the negative electrode plate, with specific O-to-Si molar ratios and controlled gram capacity, addresses the volume change issue in silicon-based lithium-ion batteries, improving cycle life and energy density.

JP2025000929AActive Publication Date: 2025-01-07CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024173227
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-10-02
Publication Date
2025-01-07
Estimated Expiration
2041-10-15

AI Technical Summary

Technical Problem

Silicon-based materials used in lithium-ion batteries experience significant volume changes during lithium release and absorption, leading to reduced cycle life and low initial coulombic efficiency, affecting energy density.

Method used

A negative electrode plate with a dual coating structure, where the first coating has a molar ratio of O element to Si element ranging from 0.5 to 1.5 and the second coating has a ratio of 0.3 or less, along with controlled weighted gram capacity and adhesive composition, to improve cycle life and energy density.

Benefits of technology

The dual coating structure enhances the cycle life and energy density of lithium-ion batteries by stabilizing volume changes and maintaining interfacial compatibility, resulting in high initial coulombic efficiency and extended battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000929000001_ABST
    Figure 2025000929000001_ABST
Patent Text Reader

Abstract

To improve a cycle life and an energy density of a lithium ion battery.SOLUTION: The present application provides a negative electrode plate, a secondary battery, a battery module, a battery pack, and a power consumption device, and contains a first coating, a second coating, and a collector. One side of the second coating is the collector, the other side of the second coating is a first coating. Both of the first and second coatings contain a silicon system material. A mole ratio of O element and Si element of the silicon system material of the first coating is 0.5 to 1.5, and the mole ratio of O element and Si element of the silicon system material of the second coating is 0.3 or less. The present application can improve a cycle life and an energy density of a battery.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of lithium battery technology, and in particular to a negative electrode plate, a secondary battery, a battery module, a battery pack, and a power consuming device. [Background technology]

[0002] Lithium-ion batteries have the characteristics of large specific energy, high operating voltage, low self-discharge rate, small volume, light weight, etc. With the rapid development of electric vehicles, people's requirements for the energy density, cycle performance, etc. of lithium-ion batteries are also increasing. Silicon-based materials have the characteristic of having high specific capacity, and are expected to be the next-generation lithium-ion anode material.

[0003] Silicon-based materials undergo a large volume change during the lithium absorption / release process, which affects the cycle life of lithium-ion batteries; moreover, the initial coulombic efficiency of silicon-based materials is low, which affects the energy density of lithium-ion batteries. Summary of the Invention

[0004] The present application has been made in view of the above-mentioned problems, and an object of the application is to improve the cycle life and energy density of lithium ion batteries.

[0005] To achieve the above object, the present application provides a negative electrode plate, a secondary battery, a battery module, a battery pack, and a power consuming device.

[0006] A first aspect of the present application provides a negative electrode plate, the negative electrode plate comprising a first coating, a second coating, and a current collector, one side of the second coating being the current collector and the other side of the second coating being the first coating, the first coating and the second coating comprising a silicon-based material, the silicon-based material of the first coating having a molar ratio of O element to Si element of 0.5 to 1.5, and the silicon-based material of the second coating having a molar ratio of O element to Si element of 0.3 or less.

[0007] Therefore, the present application aims to coordinately adjust the molar ratios of O and Si elements in the silicon-based materials in the first coating and the second coating, so that the first coating improves the cycle life of the lithium-ion battery, and the second coating improves the initial coulombic efficiency and energy density of the lithium-ion battery, thereby improving the cycle life and energy density of the lithium-ion battery.

[0008] In any embodiment, the molar ratio of O element to Si element in the silicon-based material of the second coating is 0.05 to 0.2, which can improve both the energy density and the battery cycle life of the lithium ion battery.

[0009] In any embodiment, the weighted gram capacity A1 of the first coating active material and the weighted gram capacity A2 of the second coating active material satisfy 0.8≦A1:A2≦1.2, so as to reduce the risk of film peeling occurring in the lithium ion battery throughout the life cycle of the battery, and to improve the performance and safety of the lithium ion battery.

[0010] In any embodiment, the weighted gram capacity A1 of the first coated active material is 500 mAh / g to 1000 mAh / g, and the weighted gram capacity A2 of the second coated active material is 500 mAh / g to 1000 mAh / g, resulting in a lithium ion battery having excellent cycle life and energy density.

[0011] In any embodiment, the content of the silicon-based material in the first coating is 18 wt% to 55 wt%, and the content of the silicon-based material in the second coating is 7 wt% to 21 wt%, resulting in a lithium-ion battery with excellent cycle life and energy density.

[0012] In any embodiment, the first coating includes a first adhesive and the second coating includes a second adhesive, which can improve the interfacial adhesion effect between the first coating and the second coating, further reduce the risk of peeling off of the first coating and the second coating, and improve the safety of the lithium ion battery.

[0013] In any embodiment, the first adhesive and the second adhesive each independently comprise at least one of polyacrylic acid, polyacrylate, sodium alginate, polyacrylonitrile, polyethylene glycol, carboxymethyl chitosan, and styrene butadiene rubber.

[0014] In an optional embodiment, the first adhesive and the second adhesive both include a polyacrylate adhesive, and the content of the polyacrylate adhesive in the first coating is less than that in the second coating, so as to effectively improve the energy density of the battery and reduce the cost of auxiliary materials while satisfying the adhesive effect.

[0015] In any embodiment, the content of the polyacrylate adhesive in the first coating is 3 wt%-6 wt%, and the content of the polyacrylate adhesive in the second coating is 4 wt%-7 wt%, which can effectively improve the energy density of the battery and reduce the auxiliary material cost while satisfying the adhesive effect.

[0016] A second aspect of the present application provides a secondary battery including the negative electrode plate of the first aspect of the present application.

[0017] A third aspect of the present application provides a battery module including the secondary battery of the second aspect of the present application.

[0018] A fourth aspect of the present application provides a battery pack including the battery module of the third aspect of the present application.

[0019] A fifth aspect of the present application provides a power consuming device including at least one selected from the secondary battery of the second aspect of the present application, the battery module of the third aspect of the present application, or the battery pack of the fourth aspect of the present application.

[0020] The beneficial effects of the present application are as follows:

[0021] The present application provides a negative electrode plate, a secondary battery, a battery module, a battery pack and a power consumption device, the negative electrode plate includes a first coating and a second coating, and the molar ratio of O element and Si element of the silicon-based material in the first coating and the second coating are coordinated to improve the cycle life of the lithium ion battery after the first lithium absorption, and the second coating improves the first coulombic efficiency and energy density of the lithium ion battery, thereby improving the cycle life and energy density of the lithium ion battery. Of course, any one product or method implementing the present application does not need to achieve all of the above-mentioned advantages at the same time.

[0022] In order to more clearly describe the technical solutions of the present application and the prior art, the following will briefly describe the drawings that need to be used in the embodiments and the prior art, and it is obvious that the drawings in the following description are only some embodiments of the present application. [Brief description of the drawings]

[0023] [Figure 1] FIG. 2 is a schematic diagram of a negative plate according to an embodiment of the present application. [Diagram 2] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 3] FIG. 3 is an exploded view of the secondary battery according to an embodiment of the present application shown in FIG. 2. [Figure 4] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Diagram 5] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Figure 6] FIG. 6 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG. 5. [Figure 7] 1 is a schematic diagram of a power consuming device in which a secondary battery is used as a power source according to an embodiment of the present application; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the negative electrode plate, positive electrode plate, secondary battery, battery module, battery pack, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0025] The "ranges" disclosed in this application are defined in the form of lower and upper limits, where a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the end values, and any combination is possible, i.e., any combination of any lower limit with any upper limit can form a range. For example, if ranges of 60-120 and 80-110 are recited for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. It is noted that if minimum range values ​​1 and 2 are recited, and maximum range values ​​3, 4, and 5 are recited, then ranges of 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all contemplated. In this application, unless otherwise specified, a numerical range of "a to b" represents a shorthand representation of any combination of real numbers a to b, where a and b are both real numbers. For example, a numerical range of "0-5" is meant herein to enumerate all real numbers between "0-5," and "0-5" is merely a shorthand for combinations of these numerical values. Note that expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0026] Unless otherwise stated, all the embodiments and optional embodiments in the present application can be combined with each other to form a new technical solution.

[0027] Unless otherwise stated, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0028] Unless otherwise stated, all steps in the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method mentioned above further includes step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0029] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the listed ingredients.

[0030] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the term "A or B" means "A, B, or both A and B." More specifically, any of the following conditions satisfy "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist).

[0031] In the process of researching silicon-based battery, the applicant has found that silicon-based material has a problem of large volume expansion during charging and discharging, so that the cycle life of silicon-based battery is difficult to meet the needs of application. The initial coulombic efficiency of silicon-based material is low, which affects the energy density of silicon-based battery. In order to improve the cycle life and energy density of silicon-based battery, and make silicon-based battery have better performance, such as longer driving range and longer service life, when applied to power consumption device, the present application provides a negative plate, a secondary battery, a battery module, a battery pack and a power consumption device.

[0032] In one embodiment of the present application, the present application provides a negative electrode plate, as shown in FIG. 1 , comprising a first coating 1, a second coating 2 and a current collector 3, one side of the second coating 2 is the current collector 3, and the other side of the second coating 2 is the first coating 1, the first coating 1 and the second coating 2 comprise a silicon-based material, the molar ratio of O element to Si element of the silicon-based material of the first coating 1 is 0.5-1.5, preferably 0.8-1.2, and the molar ratio of O element to Si element of the silicon-based material of the second coating 2 is not more than 0.3.

[0033] Although the mechanism is still unclear, the applicant unexpectedly discovered that the negative plate of the present application includes a first coating and a second coating, and by coordinately adjusting the molar ratio of O element to Si element of the silicon-based material in the first coating and the molar ratio of O element to Si element of the silicon-based material in the second coating, within the scope of the present application, the first coating improves the cycle life of the lithium-ion battery, and the second coating improves the initial coulombic efficiency and energy density of the lithium-ion battery, thereby overall improving the cycle life and energy density of the lithium-ion battery.

[0034] The applicant has found that, regardless of any theory, for silicon-based negative electrode materials, the higher the oxygen element content in the material, the greater the proportion of lithium oxide, lithium silicate (e.g., Li2SiO3, Li4SiO4, Li6Si2O7, etc.) components with buffering effect formed after the first cycle of lithium absorption, and the presence of these components can effectively mitigate the volume change during the lithium absorption process of the silicon-based material, effectively improve the rupture and repair degree of the solid electrolyte interface (SEI) film during the life cycle of the lithium-ion battery, thereby improving the cycle life of the lithium-ion battery. However, the presence of these components that do not have reversible lithium absorption and release reduces the reversible gram capacity of the silicon-based material, and further affects the initial coulombic efficiency of the lithium-ion battery, and to some extent impairs the energy density of the lithium-ion battery; on the other hand, the oxygen element content in the silicon-based material decreases, and the expansion of the silicon-based material increases during the lithium absorption and release process, and the capacity of the silicon-based material fades faster with the increase in the number of cycles, but the lithium-ion battery has a high initial coulombic efficiency and a high energy density.

[0035] The applicant has further discovered that, notwithstanding any theory, during the charge and discharge processes of a porous electrode, due to the presence of liquid phase ohmic polarization and diffusion polarization, the charge and discharge current is concentrated on the side of the electrode plate closer to the solution, i.e., the closer the active material particles are to the surface of the electrode plate (i.e., the electrolyte side), the greater the throughput of lithium release and lithium absorption during the charge and discharge processes carried out by the active material.

[0036] Based on this, in the present application, the first coating of the negative electrode plate is disposed close to the electrolyte, and can bear a large amount of lithium ion throughput during the battery use process, and the molar ratio of O element to Si element of the silicon-based material in the first coating is 0.5 to 1.5, and after the first cycle of lithium absorption, more active materials such as lithium oxide and lithium silicate are formed to alleviate the volume expansion, thereby improving the cycle life of the lithium ion battery; the second coating is disposed close to the current collector, and the molar ratio of O element to Si element of the silicon-based material in the second coating is 0.3 or less, and the amount of active lithium consumed during the first lithium absorption process of the negative electrode plate is reduced, and the first coulombic efficiency and energy density of the lithium ion battery can be improved. The negative electrode plate of the present application includes the above-mentioned first coating and second coating, and thus achieves high energy density, first coulombic efficiency, and long cycle life in the lithium ion battery.

[0037] In some embodiments, the silicon-based material in the first coating of the present application is a silicon-oxygen material (SiO x and the silicon-based material in the second coating may be a silicon-oxygen material or an elemental silicon material.

[0038] In some embodiments, the molar ratio of O element to Si element in the silicon-based material of the first coating is 0.8 to 1.2, and the molar ratio of O element to Si element in the silicon-based material of the second coating is 0.05 to 0.2. The present applicant has discovered that by controlling the molar ratio of O element to Si element in the silicon-based material of the first coating and the molar ratio of O element to Si element in the silicon-based material of the second coating within the above ranges, it is possible to improve both the energy density of the lithium-ion battery and the battery cycle life.

[0039] In some embodiments, the weighted gram capacity A1 of the first coating active material and the weighted gram capacity A2 of the second coating active material satisfy 0.8≦A1:A2≦1.2. In this application, the weighted gram capacity A of the active material in a coating refers to the weighted value of the reversible lithium absorption / release gram capacity of the silicon-based material in the active material of this coating and the reversible lithium absorption / release gram capacity of other active components, and the weighted gram capacity A is expressed by the formula A=Σn i x i The unit is mAh / g, where x i represents the mass ratio of the active component of the ith class to the total active material in this coating, and Σx i = 1, and n i represents the reversible gram capacity of the active ingredient of class i in this coating, in mAh / g.

[0040] The applicant has found that for a composite electrode plate containing both a carbon material and a silicon-based material, when the composition of the silicon-based material is constant, the higher the proportion of the silicon-based material, the higher the weighted gram capacity; however, the greater the repulsion of the electrode plate under the same charge state; if the difference in weighted gram capacity between the first coating and the second coating is too large, the difference in expansion stress between the first coating and the second coating during the lithium release and absorption process of the electrode plate will be too large, resulting in poor interface compatibility between the two coatings; and the first coating and the second coating may separate and peel off in a fully charged state or during the battery life cycle; therefore, some active material in the first coating may be detached from the conductive network and unable to release and absorb lithium; and furthermore, this may cause lithium precipitation due to the mismatch of the anode and cathode capacities in localized areas, which may cause performance problems and even safety problems for the lithium-ion battery.

[0041] In the present application, by controlling the ratio of the weighted gram capacity A1 of the first coating active material to the weighted gram capacity A2 of the second coating active material within the above range, when the plate releases and absorbs lithium ions under different capacity decay conditions, the first coating and the second coating maintain good interface compatibility, and the stress between the two coatings is kept within a small range, thereby reducing the risk of delamination occurring in the lithium ion battery throughout the life cycle of the lithium ion battery, and improving the performance and safety of the lithium ion battery.

[0042] In some embodiments, the weighted gram capacity A1 of the first coated active material is 500mAh / g to 1000mAh / g, and the weighted gram capacity A2 of the second coated active material is 500mAh / g to 1000mAh / g. Regardless of any theory, by controlling the weighted gram capacity A1 of the first coated active material and the weighted gram capacity A2 of the second coated active material in a coordinated manner within the above ranges, the expansion of the negative plate during cycling can be controlled within an appropriate range, and a high gram capacity can be exhibited, thereby resulting in a lithium ion battery with good cycle life and energy density.

[0043] In some embodiments, the content of the silicon-based material in the first coating is 18 wt%-55 wt%, and the content of the silicon-based material in the second coating is 7 wt%-21 wt%. Notwithstanding any theory, by controlling the content of the silicon-based material in the first coating and the content of the silicon-based material in the second coating in a coordinated manner within the above ranges, the expansion of the negative plate during cycling can be controlled within an appropriate range, and the negative plate can also have a high gram capacity, thereby resulting in a lithium ion battery with good cycle life and energy density.

[0044] In some embodiments, the first coating includes a first adhesive and the second coating includes a second adhesive. In the present application, the first adhesive and the second adhesive may be similar or different. By adding the first adhesive to the first coating and the second adhesive to the second coating, the interface adhesion effect of the first coating and the second coating can be improved, the risk of the first coating and the second coating being peeled off can be further reduced, and the safety of the lithium-ion battery can be improved.

[0045] In the present application, there are no particular limitations on the first adhesive and the second adhesive, as long as the object of the present application can be achieved. In some embodiments, the first adhesive and the second adhesive each independently include at least one of polyacrylic acid, polyacrylate, sodium alginate, polyacrylonitrile, polyethylene glycol, carboxymethyl chitosan, and styrene butadiene rubber.

[0046] In some embodiments, the first adhesive and the second adhesive both include a polyacrylate-based adhesive, and the content of the polyacrylate-based adhesive in the first coating is less than that in the second coating. When the first coating and the second coating of the negative electrode plate of the present application include a silicon-based material, and the first adhesive and the second adhesive both include a polyacrylate-based adhesive, the polyacrylate-based adhesive can form strong hydrogen bonds with the silicon-based material and effectively cover the surface of the silicon-based material, thereby mitigating the volume expansion of the silicon-based material during charging and discharging. The applicant has found that since the silicon-based material in the first coating has a high oxygen-silicon molar ratio and a smaller volume expansion during the lithium-ion battery cycle than the second coating, the content of the polyacrylate-based adhesive in the first coating can be controlled to be less than that in the second coating, thereby improving the energy density of the battery and reducing the cost of auxiliary materials while satisfying the adhesive effect.

[0047] In some embodiments, the content of the polyacrylate adhesive in the first coating is 3wt%-6wt%, and the content of the polyacrylate adhesive in the second coating is 4wt%-7wt%. The applicant is not limited by any theory, but believes that by controlling the content of the polyacrylate adhesive in the first coating and the second coating within the above range, the energy density of the battery can be effectively improved and the auxiliary material cost can be reduced while satisfying the adhesion effect.

[0048] In the present application, there is no particular limitation on the method for producing the silicon-based material, and the silicon-based material can be produced, for example, by the following steps.

[0049] The silicon dioxide powder and the elemental silicon powder may be obtained by a high-temperature gas phase reaction in a non-oxidizing gas atmosphere, and the ratio of the silicon dioxide powder and the elemental silicon powder may be adjusted to adjust the elemental ratio of oxygen and silicon in the obtained silicon-based material. In the present application, there is no particular limitation on the particle size of the silicon dioxide powder and the elemental silicon powder, and it is sufficient to satisfy the requirements of the present application. For example, the average particle size of the silicon dioxide powder is 1 μm to 10 μm, and the average particle size of the elemental silicon powder is 1 μm to 10 μm. In the present application, there is no particular limitation on the non-oxidizing gas atmosphere, and it may be, for example, an argon gas or hydrogen gas atmosphere. In the present application, there is no particular limitation on the temperature of the gas phase reaction, and it is sufficient to satisfy the requirements of the present application. For example, the temperature is 1300 ° C to 1400 ° C.

[0050] In some embodiments, the silicon oxygen materials produced may be further coated or composited with other active materials for use in lithium ion batteries.

[0051] The secondary battery, the battery module, the battery pack, and the power consuming device of the present application will be described below with appropriate reference to the drawings.

[0052] In one embodiment of the present application, a secondary battery is provided, the secondary battery including the negative electrode plate according to any one of the above embodiments. The secondary battery of the present application may be the lithium ion battery according to any one of the above embodiments.

[0053] Typically, a secondary battery includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During the charge and discharge process of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to perform intercalation and deintercalation. The electrolyte serves to conduct ions between the positive electrode plate and the negative electrode plate. The separator is provided between the positive electrode plate and the negative electrode plate, and serves mainly to prevent short-circuiting between the positive and negative electrodes, while allowing ions to pass through.

[0054] [Positive plate] The positive electrode plate includes a positive electrode current collector and a positive electrode material provided on at least one surface of the positive electrode current collector. As an example, the positive electrode current collector has two surfaces facing each other in the thickness direction of the positive electrode current collector, and the positive electrode film layer is provided on either one or both of the two facing surfaces of the positive electrode current collector.

[0055] In the lithium ion battery of the present application, the positive electrode current collector may adopt a metal foil sheet or a composite current collector. For example, an aluminum foil may be adopted as the metal foil sheet. The composite current collector may include a polymeric material base layer and a metal layer formed on at least one surface of the polymeric material base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0056] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of the lithium transition metal oxide include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (may be abbreviated as LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 (may be abbreviated as LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (may be abbreviated as LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM 622 (may be abbreviated as LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.

[0057] In some embodiments, the positive electrode membrane layer optionally further comprises an adhesive. For example, the adhesive may comprise at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic ester resin.

[0058] In some embodiments, the positive electrode membrane layer optionally further comprises a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example only.

[0059] In some embodiments, a positive electrode plate can be manufactured in the following manner: the components for manufacturing a positive electrode plate, such as the positive electrode active material, conductive agent, adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is applied to a positive electrode current collector, followed by processes such as drying and cold pressing to obtain a positive electrode plate.

[0060] [Negative plate] In some embodiments, the negative electrode current collector of the negative electrode plate may employ a metal foil sheet or a composite current collector. For example, a copper foil may be employed as the metal foil sheet. The composite current collector may include a polymeric material base layer and a metal layer formed on at least one surface of the polymeric material substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0061] In some embodiments, a negative electrode plate can be manufactured in the following manner: a first negative electrode slurry and a second negative electrode slurry are manufactured, the second negative electrode slurry is first applied to a second coating formed on a current collector, and then the first negative electrode slurry is applied to the first coating formed on the surface of the second coating; or a two-layer coating device can be used during coating to simultaneously coat the first negative electrode slurry and the second negative electrode slurry on the current collector, and a negative electrode plate is obtained through processes such as drying and cold pressing, in which one side of the second coating is the current collector and the other side of the second coating is the first coating.

[0062] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative plates. The present application does not specifically limit the type of electrolyte, and it can be selected according to needs. For example, the electrolyte may be liquid, gel, or all solid.

[0063] In some embodiments, the electrolyte employs an electrolyte solution, the electrolyte solution including an electrolyte salt and a solvent.

[0064] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonimide, lithium bistrifluoromethanesulfonimide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, and lithium tetrafluoro(oxalato)phosphate.

[0065] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.

[0066] In some embodiments, the electrolyte solution optionally further includes additives. For example, the additives may include an anode film-forming additive and a cathode film-forming additive, and may further include additives that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature or low temperature performance of the battery, etc.

[0067] [Separator] In some embodiments, the secondary battery further includes a separator. The present application does not particularly limit the type of separator, and any well-known separator with a porous structure having good chemical stability and mechanical stability may be selected.

[0068] In some embodiments, the separator may be made of at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layered thin film or a multi-layered composite thin film, without any particular limitation. When the separator is a multi-layered composite thin film, the materials of each layer may be the same or different, without any particular limitation.

[0069] In some embodiments, the positive and negative plates and the separator may be fabricated into an electrode assembly by a winding or lamination process.

[0070] In some embodiments, the secondary battery may include an exterior packaging, which may be used to package the electrode assembly and electrolyte.

[0071] In some embodiments, the exterior of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The exterior of the secondary battery may be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as polypropylene, polybutylene terephthalate, or polybutylene succinate.

[0072] In the present application, there is no particular limitation on the shape of the secondary battery, which may be cylindrical, rectangular, or any other shape. For example, FIG. 2 shows a secondary battery 5 having a rectangular structure as an example.

[0073] In some embodiments, referring to FIG. 3, the exterior may include a housing 51 and a cover plate 53. Here, the housing 51 may include a bottom plate and a side plate connected on the bottom plate, and the bottom plate and the side plate surround the housing 51 to form a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be provided to cover the opening to close the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte permeates the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be selected by those skilled in the art according to actual specific needs.

[0074] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, with the specific number being selectable by one of ordinary skill in the art based on the application and capacity of the battery module.

[0075] Fig. 4 shows an example of a battery module 4. Referring to Fig. 4, in the battery module 4, the secondary batteries 5 may be arranged in sequence along the vertical direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the secondary batteries 5 may be fixed by a fastener.

[0076] Optionally, the battery module 4 may further include a housing having an accommodation space for accommodating a plurality of secondary batteries 5.

[0077] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number may be selected by one skilled in the art based on the application and capacity of the battery pack.

[0078] 5 and 6 show an example of a battery pack 10. Referring to Fig. 5 and 6, the battery pack 10 may include a battery case and a plurality of battery modules 4 arranged in the battery case. The battery case includes an upper case 11 and a lower case 12, and the upper case 11 is arranged to cover the lower case 12 and can form an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery case in any manner.

[0079] The present application further provides a power consuming device including at least one of the secondary battery, battery module, or battery pack according to the present application. The secondary battery, battery module, or battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile equipment (e.g., mobile phone, laptop, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0080] The power consuming device may be a secondary battery, a battery module, or a battery pack, depending on the needs of the usage.

[0081] 7 shows an example of a power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. The power consuming device can use a battery pack or a battery module to meet the demand for high power and high energy density from secondary batteries.

[0082] Another example of the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such devices are generally required to be lightweight and may employ a secondary battery as a power source.

[0083] Working Example The following describes the examples of the present application. The examples described below are illustrative and are used only to interpret the present application, and should not be understood as limiting the present application. In the examples, specific techniques or conditions are not specified, but are carried out according to the techniques or conditions described in the technical literature or product instructions. For reagents or equipment used, those without the manufacturer are all common products that can be purchased commercially.

[0084] Example 1 <Production of positive electrode plates> Positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added as a solvent. The system is stirred to a homogeneous state by a vacuum mixer to obtain a positive electrode slurry with a solid content of 75 wt%. The positive electrode slurry is uniformly applied to one surface of an aluminum foil with a thickness of 12 μm, dried at 120°C, and cold pressed to obtain a positive electrode plate with a positive electrode active material layer thickness of 60 μm. The positive electrode plate is then obtained through processes such as tab forming and slit processing.

[0085] <Production of negative electrode plates> <Preparation of first negative electrode slurry> The first negative electrode active material, the carbon material artificial graphite, the conductive agent conductive carbon black, and the adhesive sodium polyacrylate are mixed in a mass ratio of 18:77:2:3, deionized water is added as a solvent, and the system is stirred by a vacuum mixer until it becomes uniform, to obtain a first negative electrode slurry with a solid content of 50 wt%.

[0086] <Preparation of second negative electrode slurry> The second negative electrode active material, the carbon material artificial graphite, the conductive agent conductive carbon black, and the adhesive sodium polyacrylate are mixed in a mass ratio of 7:87:2:4, deionized water is added as a solvent, and the system is stirred by a vacuum mixer until it becomes uniform, to obtain a second negative electrode slurry with a solid content of 50 wt%.

[0087] <Manufacture of negative electrode plate including first coating and second coating> A two-layer coating process is adopted, and the first and second negative electrode slurries thus produced are coated on one surface of a copper foil with a thickness of 8 μm, dried at 110°C, and cold pressed to obtain a negative electrode plate with a first coating thickness and a second coating thickness of 25 μm respectively, and then the negative electrode plate is obtained through processes such as tab forming and slit processing.

[0088] <Electrolyte production> In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and then lithium salt LiPF6 is dissolved in the mixed solvent to produce an electrolyte with a lithium salt concentration of 1 mol / L.

[0089] <Separator manufacturing> A polyethylene film with a thickness of 9 μm is selected as the separator, and before use, it is slit to obtain an appropriate width according to the size of the positive and negative electrode plates.

[0090] <Lithium-ion battery manufacturing> A positive electrode plate, a separator, and a negative electrode plate are stacked in this order, and a separator is interposed between the positive electrode plate and the negative electrode plate to serve as an insulator. The stack is then wound to obtain an electrode assembly. The electrode assembly is then placed in an exterior housing, dried, and then an electrolyte is injected. The lithium-ion battery is then obtained through processes such as vacuum packaging, standing, chemical formation, and shaping.

[0091] Examples 2 to 11 In <Production of negative electrode plate>, the molar ratio of O element to Si element in the first negative electrode slurry and the molar ratio of O element to Si element in the second negative electrode slurry were adjusted as shown in Table 1, the values ​​of A1, A2, and A1:A2 were adjusted as shown in Table 2, and the ratio of the first negative electrode active material in the first slurry, the ratio of the second negative electrode active material in the second slurry, the type and ratio of the adhesive in the first slurry, the type and ratio of the adhesive in the second slurry, the ratio of the artificial graphite and conductive carbon black in the first negative electrode slurry, and the ratio of the artificial graphite and conductive carbon black in the second negative electrode slurry were adjusted as shown in Table 3. Other than that, the same as in Example 1.

[0092] Example 12 In <Preparation of Positive Electrode Plate> and <Preparation of Negative Electrode Plate>, the positive electrode active material layer and the negative electrode active material layer are respectively formed by a double-sided coating process, that is, active material layers are formed on both sides of the positive electrode current collector and the negative electrode current collector, respectively, and the rest is the same as in Example 1, and the active material layers on both sides of the negative electrode current collector each include a first coating and a second coating, respectively.

[0093] Comparative Example 1 Except for the difference in <Production of the negative electrode plate> from Example 2, the rest is the same as Example 2.

[0094] <Production of negative electrode plates> The first negative electrode slurry and the second negative electrode slurry of Example 2 are mixed in a mass ratio of 1:1 to obtain a mixed slurry, which is then coated on one surface of a copper foil having a thickness of 8 μm, dried under a condition of 110° C., and cold pressed to obtain a negative electrode plate having a negative electrode active material layer having a thickness of 50 μm, and then processed through processes such as tab forming and slit processing to obtain a negative electrode plate.

[0095] Comparative Examples 2 to 6 In <Production of negative electrode plate>, the molar ratio of O element to Si element in the first negative electrode slurry and the molar ratio of O element to Si element in the second negative electrode slurry were adjusted as shown in Table 1, the values ​​of A1, A2, and A1:A2 were adjusted as shown in Table 2, and the ratio of the first negative electrode active material in the first slurry, the ratio of the second negative electrode active material in the second slurry, the type and ratio of the adhesive in the first slurry, the type and ratio of the adhesive in the second slurry, the ratio of the artificial graphite and conductive carbon black in the first negative electrode slurry, and the ratio of the artificial graphite and conductive carbon black in the second negative electrode slurry were adjusted as shown in Table 3. Other than that, the same as in Example 1.

[0096] The relevant parameters of the above Examples 1 to 12 and Comparative Examples 1 to 6 are as shown in the following Tables 1 to 3. Here, the molar ratio of O element to Si element in the first negative electrode slurry and the molar ratio of O element to Si element in the second negative electrode slurry are shown in Table 1, the values ​​of A1, A2, and A1:A2 are shown in Table 2, and the ratio of the first negative electrode active material in the first slurry, the ratio of the second negative electrode active material in the second slurry, the type and ratio of the adhesive in the first slurry, the type and ratio of the adhesive in the second slurry, the ratio of the artificial graphite and the conductive carbon black in the first negative electrode slurry, and the ratio of the artificial graphite and the conductive carbon black in the second negative electrode slurry are shown in Table 3.

[0097] [Table 1]

[0098] [Table 2]

[0099] [Table 3]

[0100] In addition, the lithium ion batteries manufactured in the above Examples 1 to 12 and Comparative Examples 1 to 6, and the negative electrode active materials using the above Examples 1 to 12 and Comparative Examples 1 to 6 are manufactured into button batteries, and performance tests are carried out. The test results are shown in Table 4 below.

[0101] Energy Density Test: The test temperature was 25°C. The lithium ion batteries prepared in each embodiment and comparative example were first charged at a constant current of 0.33C to 4.25V, then charged at a constant voltage of 0.05C, and allowed to stand for 5 minutes, and then discharged at 0.33C to 2.8V. The discharge energy was recorded, and the discharge energy density at 0.33C was calculated according to the following formula: energy density (Wh / kg) = discharge energy (Wh) / weight of electrochemical device (kg).

[0102] Cycle Life Test: The test temperature is 25°C, and the lithium ion batteries manufactured in each Example and Comparative Example are charged at a constant current of 0.33C to 4.25V, then charged at a constant voltage of 0.05C, left to stand for 10 minutes, and discharged at 0.33C to 2.8V. The capacity obtained in this step is the initial capacity, and the battery is charged at a constant current of 0.33C to 4.25V, charged at a constant voltage of 0.05C at 4.25V, and discharged at 0.33C to 2.8V, and a cycle test is performed to obtain a capacity decay curve based on the ratio of the capacity at each step to the initial capacity. The number of cycles at 25°C until the capacity retention rate reaches 80% is recorded as the cycle life of the battery.

[0103] First charge / discharge efficiency test: The lithium ion batteries manufactured in each of the examples and comparative examples are subjected to a charge-discharge test using a Neware CT-4000 power battery testing system, and the initial charge-discharge efficiency of the lithium ion batteries is calculated.

[0104] The calculation method for the initial efficiency is (C1 / C2)×100%, where C1 is the capacity of the lithium-ion battery at the initial charge, and the charging flow is constant current charging at 0.33C until the voltage reaches 4.25V, and then constant voltage charging at 0.05C at 4.25V; C2 is the corresponding capacity when the lithium-ion battery is discharged at 0.33C until the voltage reaches 2.8V after the initial charging according to the flow.

[0105] Weighted Gram Capacity Test: The weighted gram capacities of different coatings on the negative electrode plates in Examples 1 to 12 and Comparative Examples 1 to 6 are obtained by the following method.

[0106] The negative active material (e.g., silicon-based material, artificial graphite material) is mixed with the conductive carbon black of the conductive agent and the PVDF (polyvinylidene fluoride) of the adhesive in a ratio of 80:10:10, and deionized water is added and stirred to form a slurry with a solid content of 50wt%, and a doctor blade is used to apply a coating of 50μm thickness to the surface of the current collector, and after drying in a vacuum drying box under the condition of 85℃ for 12 hours, a punching machine is used to cut into wafers with a diameter of 1cm in a dry environment, and in a glove box, a lithium metal plate is selected as the counter electrode, and a PE (polyethylene) composite film is selected as the separator, and an electrolyte is added to assemble into a button battery, and the reversible gram capacity of such active components tested by the method of charge and discharge test is calculated. The weighted gram capacity of the active material of the first coating or the second coating is calculated by the following formula: A=x1×n1+x2×n2(mAh / g). where x1 and x2 are the mass ratios of the silicon-based material and the carbon material in the active materials, respectively, and x1+x2=1; n1 represents the reversible gram capacity of the silicon-based material, with the unit being mAh / g; and n2 represents the reversible gram capacity of the artificial graphite material, with the unit being mAh / g.

[0107] [Table 4]

[0108] As can be seen from the above results, the negative electrode plate of the lithium ion battery of Examples 1 to 12 includes a first coating and a second coating, that is, has a multi-layer structure, where one side of the second coating is a current collector, and the other side of the second coating is the first coating. The molar ratio of O element to Si element of the silicon-based material in the first coating and the second coating is within the scope of the present application, and the lithium ion battery has excellent energy density and initial coulombic efficiency as well as long cycle life.

[0109] As can be seen from Examples 1 to 4, after the element ratio of oxygen to silicon in the silicon-based material in each coating of the negative plate is determined, with the increase in the content of silicon-based material in the negative plate, the weighted gram capacity performance of the negative plate is improved, and further the energy density of the lithium ion battery is improved.

[0110] As can be seen from Examples 2, 5, 6 and 9, when the ratio of silicon-based material in each coating of the negative plate is relatively constant, with an increase in the elemental molar ratio of oxygen to silicon in the silicon-based material in the first coating and the second coating, the lithium-ion battery shows a tendency of improving the cycle life and decreasing the energy density and initial coulombic efficiency, but the magnitude of the decrease is not obvious.

[0111] As can be further seen from Examples 1 to 12, by controlling the ratio of silicon-based materials in each coating, when the ratio A1:A2 of the weighted gram capacity A1 of the first coating to the weighted gram capacity A2 of the second coating is within the range of the present application, it is possible to achieve a lithium ion battery with both high energy density, high initial coulombic efficiency and long cycle life.

[0112] As can be further seen from Examples 1-9, 11-12, when both the first coating and the second coating use a polyacrylate-based adhesive (e.g., sodium polyacrylate), when the content of the polyacrylate-based adhesive in the first coating is less than that in the second coating, the lithium ion battery has a longer cycle life.

[0113] The type and content of the adhesive in the first coating and the second coating also generally affect the performance of the lithium-ion battery. As can be seen from Examples 1 to 12, if the type and content of the adhesive are within the range of this application, a lithium-ion battery having excellent energy density and initial coulombic efficiency as well as long cycle life can be obtained.

[0114] In contrast, the negative plate of Comparative Example 1 was obtained by uniformly mixing the first coating slurry and the second active coating slurry of Example 2 and then coating the mixture, and the type and composition of the silicon-based material of the negative plate in the direction perpendicular to the current collector are the same, so the energy density and initial coulombic efficiency of Comparative Example 1 are substantially consistent with those of Example 2. However, since the lithium ion battery does not have the double coating structure of the present application, the reversible capacity of the silicon-based material (i.e., the second negative active material) with an oxygen to silicon element ratio of 0.1:1 close to the current collector surface is rapidly attenuated during cycling, so the cycle life of the lithium ion battery of Comparative Example 1 is only 550 cycles, and the cycle life is not effectively improved, making it difficult to meet the needs for lithium ion battery life in many application scenarios.

[0115] The molar ratio of oxygen to silicon in the silicon-based materials in the first and second coatings used in Comparative Example 2 was both 1:1, and the initial coulombic efficiency of the resulting lithium-ion battery was reduced to 72%, and the energy density of the lithium-ion battery could only reach 250Wh / kg. Compared with lithium-ion batteries that do not use silicon-based materials in the negative electrode, the energy density does not have a significant advantage, making it difficult to meet the needs of situations where high energy density is required.

[0116] The molar ratio of oxygen to silicon in the first coating and the second coating used in the negative electrode plate of Comparative Example 3 is opposite to that in Example 2. The resulting lithium ion battery has a rapid reversible capacity decay during cycling, and the cycle life of the lithium ion battery is only 200 cycles. The cycle life is not effectively improved, making it difficult to meet the needs of lithium ion battery life in many application scenarios.

[0117] The oxygen to silicon element ratio of the silicon-based material in the first coating used in Comparative Example 4 was 1.85:1. The initial coulombic efficiency of the resulting lithium-ion battery was very low, and the battery energy density was only 250Wh / kg. This did not offer any advantages over lithium-ion batteries that did not use silicon-based materials, and it was difficult to meet the needs of situations requiring high energy density.

[0118] The ratio of the weighted gram capacity A1 of the first coating to the weighted gram capacity A2 of the second coating of the negative electrode plate in Comparative Examples 5 and 6 is outside the scope of the present application, which causes the cycle life of the lithium ion battery to decrease. This may be due to the fact that in the lithium absorption / discharge process of the lithium ion batteries in Comparative Examples 5 and 6, the difference in expansion stress between the first coating and the second coating is large, the interface compatibility between the first coating and the second coating is poor, or some areas of the first coating are detached from the second coating, which causes some active materials in the first coating to be detached from the conductive network during cycling, which affects the cycle life of the lithium ion battery.

[0119] It should be explained that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and having the same action and effect within the scope of the technical proposal of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can conceive of to the embodiment are implemented within the scope of the gist of the present application, and other forms constructed by combining some of the components in the embodiment are also included in the scope of the present application.

[0120] The present invention may further include the following aspects. [1] A negative electrode plate comprising a first coating, a second coating, and a current collector, one side of the second coating being the current collector and the other side of the second coating being the first coating, the first coating and the second coating containing a silicon-based material, the silicon-based material of the first coating having a molar ratio of O element to Si element of 0.5 to 1.5, and the silicon-based material of the second coating having a molar ratio of O element to Si element of 0.3 or less. [2] The negative electrode plate according to [1], wherein the molar ratio of O element to Si element in the silicon-based material of the second coating is 0.05 to 0.2. [3] The negative electrode plate according to [1] or [2], wherein the weighted gram capacity A1 of the first coating active material and the weighted gram capacity A2 of the second coating active material satisfy 0.8≦A1:A2≦1.2. [4] The negative electrode plate according to [3], wherein the weighted gram capacity A1 of the first coated active material is 500 mAh / g to 1000 mAh / g, and the weighted gram capacity A2 of the second coated active material is 500 mAh / g to 1000 mAh / g. [5] The negative electrode plate according to any one of [1] to [4], wherein the content of the silicon-based material in the first coating is 18 wt% to 55 wt%, and the content of the silicon-based material in the second coating is 7 wt% to 21 wt%. [6] The negative electrode plate according to any one of [1] to [5], wherein the first coating contains a first adhesive, and the second coating contains a second adhesive. [7] The negative electrode plate according to [6], wherein the first adhesive and the second adhesive each independently contain at least one of polyacrylic acid, a polyacrylate, sodium alginate, polyacrylonitrile, polyethylene glycol, carboxymethyl chitosan, and styrene butadiene rubber. [8] The negative electrode plate according to [6], wherein the first adhesive and the second adhesive both contain a polyacrylate-based adhesive, and a content of the polyacrylate-based adhesive in the first coating is less than a content of the polyacrylate-based adhesive in the second coating. [9] The negative electrode plate according to [8], wherein the content of the polyacrylate-based adhesive in the first coating is 3 wt% to 6 wt%, and the content of the polyacrylate-based adhesive in the second coating is 4 wt% to 7 wt%.

[10] A secondary battery comprising the negative electrode plate according to any one of [1] to [9].

[11] A battery module including the secondary battery according to

[10] .

[12] A battery pack comprising the battery module according to

[11] .

[13] A power consuming device comprising at least one selected from the secondary battery described in

[10] , the battery module described in

[11] , or the battery pack described in

[12] . [Explanation of symbols]

[0121] 1 first coating, 2 second coating, 3 current collector, 4 battery module, 5 secondary battery, 10 battery pack, 11 upper case, 12 lower case, 51 housing, 52 electrode assembly, 53 cover plate.

Claims

1. A negative electrode plate comprising a first coating, a second coating, and a current collector, one side of the second coating being the current collector and the other side of the second coating being the first coating, the first coating and the second coating comprising a silicon-based material, the silicon-based material of the first coating having a molar ratio of O element to Si element of 0.5 to 1.5, and the silicon-based material of the second coating having a molar ratio of O element to Si element of 0.3 or less, A negative electrode plate, wherein the content of the silicon-based material in the first coating is 18 wt % to 55 wt %, and the content of the silicon-based material in the second coating is 7 wt % to 21 wt %.

2. 2. The negative electrode plate according to claim 1, wherein the molar ratio of O element to Si element in the silicon-based material of the second coating is 0.05 to 0.

2.

3. Weighted Gram Capacity A of First Coated Active Material 1 and the weighted gram capacity A of the second coating active material 2 Between and 0.8≦A 1 :A 2 The negative electrode plate according to claim 1 or 2, which satisfies ≦1.

2.

4. the weighted gram capacity A of the first coated active material; 1 is 500 mAh / g to 1000 mAh / g, and the weighted gram capacity A of the second coated active material is 2 The negative electrode plate according to claim 3, wherein the capacity is 500 mAh / g to 1000 mAh / g.

5. The negative plate of any one of claims 1 to 4, wherein the first coating comprises a first adhesive and the second coating comprises a second adhesive.

6. 6. The negative plate of claim 5, wherein the first adhesive and the second adhesive each independently include at least one of polyacrylic acid, polyacrylate, sodium alginate, polyacrylonitrile, polyethylene glycol, carboxymethyl chitosan, and styrene butadiene rubber.

7. 6. The negative electrode plate of claim 5, wherein the first adhesive and the second adhesive both comprise a polyacrylate-based adhesive, and the content of the polyacrylate-based adhesive in the first coating is less than the content of the polyacrylate-based adhesive in the second coating.

8. 8. The negative electrode plate of claim 7, wherein the content of the polyacrylate adhesive in the first coating is 3 wt % to 6 wt %, and the content of the polyacrylate adhesive in the second coating is 4 wt % to 7 wt %.

9. A secondary battery comprising the negative electrode plate according to any one of claims 1 to 8.

10. A power consuming device comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2006107912A

  • Negative electrode for lithium ion secondary battery, its manufacturing method, and lithium ion secondary battery using it

    JP2006164954A

  • Negative electrode for lithium ion secondary battery, its manufacturing method, and lithium ion secondary battery using it

    JP2006196447A

  • Negative electrode for lithium secondary battery and manufacturing method thereof, as well as lithium secondary battery equipped with negative electrode for lithium secondary battery

    JP2008258154A

  • Negative electrode for nonaqueous electrolyte secondary batteries

    WO2015045341A1